Liquid metaphors as positive evaluations: A corpus-assisted discourse analysis of the representation of migrants in a daily New Zealand newspaper. (September 2016) - Salahshour, Neda
Abstract: This paper reports on the discursive construction of immigrants in newspaper articles published during 2007 and 2008 in a prominent daily newspaper in Auckland, New Zealand׳s most migrant populated city. The study adopts a corpus-assisted approach to the study of discourse (Baker et al., 2008 ; Hardt-Mautner, 1995;Partington, 2004 ) and is informed by the notion of collocation analysis. Concordances containing the collocation of one of the terms migrant(s), immigrant(s), and Asians and a liquid metaphor were examined. A focus on liquid metaphors allows comparison with previous work on the use of liquid metaphors in the representation of immigrants. The analysis shows that liquid metaphors are used to construct mass immigration not only in negative ways as suggested in previous research, but that they can also be used to reflect the positive economic impact of mass immigration on New Zealand. The paper concludes by critically discussing the various factors influencing the representation of immigrants in the New Zealand context. Highlights: The interpretation of liquid metaphors greatly depends not only on their specific co-text, but more importantly, on the contribution of a range of socio-political, and geographical factors. Liquid metaphors are not always used to construct the process of immigration as destructive, and uncontrollable but depending on the socio-political context can be used to highlight the positive economic aspects of immigration.